Mobile-Based Learning Media Using Open Ended Learning Approaches to Increasing Students' Interest in Basic Programming Subjects of Vocational Schools - Taqiyuddin, Hanan; Al Idrus, Shofiyah; Wijarnaka, Sentot (Universitas Negeri Malang, 2022)
The current developments have ease in accessing information which is a challenge for students. One form of development of the times is the use of smartphones, where these smartphones can be used by students in accessing learning resources to assist the learning process. This research utilizes the use of this smartphone to design a mobile-based learning media using the Design Thinking development method to determine the feasibility of learning media applications on basic programming materials using the Open-Ended Learning approach and to determine the level of interest in learning of senior high school student’s competency skills in Software Engineering with using a Likert scale of 4 and the User Experience Questionnaire (UEQ) method. The data collection process was carried out by distributing questionnaires to media experts, material experts, small group tests and field tests. It is hoped that this learning medium will provide a good experience for users. The conclusions obtained in the media expert validation test produce an average percentage value of 84.7 percent and in the material expert validation test produce an average percentage value of 85.00 percent. The small group produced the highest scale on stimulation with an average of 1.95 and the smallest scale on novelty with an average of 1.28. The field test produced the highest scale on stimulation with an average of 2.01 and the smallest scale on novelty with an average of 1.47. And the interest level test produces an average value of 80.68 percent which is a high interest category.